The FASB's and IASB's New Revenue Recognition Standard: What Will Be the Effects on Earnings Quality, Deferred Taxes, Management Compensation, and on Industry‐Specific Reporting?. Issue 6 (October 2016) - Rutledge, Robert W.; Karim, Khondkar E.; Kim, Taewoo
Abstract : The Financial Accounting Standards Board (FASB) and International Accounting Standards Board (IASB) have been working for 13 years on a significantly different, converged standard for revenue recognition. The new standard was finally approved by both boards in 2014, and was to be effective for calendar‐year companies beginning in 2017. On July 9, 2015, mounting concerns from preparers resulted in a one‐year delay in implementation. An important consideration to examine is "what are the major indirect effects that may result from the adoption of the new revenue recognition standard?" We discuss such effects on earnings quality, deferred taxes, management compensation, and on industry‐specific reporting. Earnings quality may be reduced because the new standard will increase deferred tax balances, and provide executives with increased opportunity to manage earnings. Alternatively, the consistency in generally accepted accounting practices (GAAP), and comparability of revenue recognition practices across industries with similar transactions may improve earnings quality. The likely cumulative effect on earnings quality is not yet determinable. Second, management may have more opportunity to manipulate earnings through judgments and estimates, and accelerate earnings‐based compensation. Thus, the standard may impact management compensation. Finally, we discuss industries that are likely to be the most impacted from the new standard. © 2016 Wiley Periodicals, Inc.